Co-Existent Hypertension with Diabetes Mellitus Exacerbates Renal Dysfunctions - Eruore Amalaka Obore; Jerome Ndudi Asiwe; Vincent I Iyawe; Andrew E. Edo (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2022)
Hypertension as well as diabetes mellitus has been reported to be a major risk factor for deteriorating kidney functions. However, there is paucity of reports on renal functions in a co-existence of hypertension and diabetic condition, hence, this study evaluates renal functions in hypertensive and diabetic co-morbidity. Participants were categorised into healthy, hypertension, diabetes and hypertension with diabetes group. Blood pressure was measured as well as fasting blood glucose and blood samples were collected from each participant to assay renal function indices. The results showed that there was substantial uraemia as well as a significant reduction glomerular filtration rate in co-morbid hypertension and diabetic patients. Fasting blood glucose and mean arterial blood pressure were considerably elevated while creatinine concentration was not significantly altered in comorbid hypertension and diabetic patients. This study revealed that co-existence of hypertension and diabetes mellitus exacerbated renal dysfunction comparatively to hypertension and diabetes mellitus.